Analisis Laporan Keberlanjutan Studi Komparasi Bank Syariah Indonesia dan Maybank Islamic Berhad 2019-2022 - Adirestuty, Fitranty; Azizah Al Adawiyah, Rumaisah; Tri Ratnasari, Ririn; Nur Chazanah, Indah; Muhammad Irsyad, Syaiful (Jurnal Ilmiah Ekonomi Islam, 2024)
This study emphasizes the importance of focusing on the sustainability and alignment of Sharia compliance disclosures in the context of Islamic Financial Institutions. Sustainability reporting is becoming increasingly crucial in the financial sector due to growing awareness of global environmental, social, and governance (ESG) issues. The initiative encourages Islamic Financial Institutions (IFIs) to increase transparency and accountability in their sustainability practices. This study tries explicitly to compare the Sustainability Report Analysis between Bank Syariah Indonesia and Maybank Islamic Berhad for 2019-2022. In this way, the study provides a deeper understanding of how these two institutions manage sustainability and disclosure of Sharia compliance. By aligning Sharia compliance with sustainability goals, IFIS can actively create a more responsible and ethical financial sector. This will contribute to broader sustainable development efforts, including sustainable economic growth, environmental protection, and Social Empowerment. This kind of research is essential to ensure that IFIs and other financial institutions understand and adhere to sustainability and Sharia compliance in a balanced manner to balance financial, ethical, and sustainability goals in their services to society.